Optimal crop planning under climate change effect using CROPWAT model in canal command area - SACHAN, SHIKHA; CHANDOLA, V. K. (Journal of Soil and Water Conservation, 2020)
Rainfall is the most important natural source of water in agriculture sector. Rainfall of Maharashtra state is highly variable with respect to time and space both and about 80-90% of precipitation falls during monsoon period. CROPWAT 8.0 model was used to estimate the net irrigation water requirement of major crops grown in different sub commands viz. BM48, BM49, BM50, BM51, BM61 and BM68 of the upper Bhima basin. Net irrigation requirement of crops were estimated using the data of available raingauges in the command. Amount of monthly dry year rainfall was evaluated by estimating probability of annual rainfall at 50% and 80% using rainfall of 28 years from 1975 to 2002. Finally, net irrigation requirement of crops; Wheat, Sorghum, Pearl millet, Green manure, Groundnut (kharif), Cotton, Chilli, Groundnut (summer) and Sugarcane were estimated for each sub-command. Again CROPWAT model was used to estimate the reference crop evapotranspiration (ET0) with the help of meteorological data of 13 years (1993-2005). The average effective rainfall was found higher in BM50 (355.8 mm) and lower in BM68 (208.6 mm), whereas maximum and minimum ET0 ranged between 7.72 mm/day to 3.10 mm/day during April and December, respectively. The dry year net irrigation water requirement of annual crop, rabi, bi-seasonal (rabi and kharif) and summer season were 9764.5, 4189.6, 8781.6 and 3376.4 mm, respectively. From this study, it is concluded that the crop selection is the most important factor for optimal irrigation planning under limited water availability situation in the canal command area of upper Bhima basin.